REPRODUÇÃO INDUZIDA DE PIAU CORRÓ (Leporinus lacustris), COM DIFERENTES INDUTORES HORMONAIS - TAVARES, Tainara Vieira,; ACUNHA, Rubia Mara Gomes3 (rubia.zootec18@gmail.com,; SANTOS, Jussara Garrido,; WANDERLEY, Alysson Martins,; COSTA, Deliane Cristina,; AMARAL, Cristiane Meldau de Campos, (ANAIS DO ENIC, 2023)
-